Defense strategies and associated phytohormonal regulation in Brassica plants in response to chewing and sap-sucking insects - Ali, Jamin; Tonğa, Adil; Islam, Tarikul; Mir, Sajad; Mukarram, Mohammad; Konôpková, Alena Sliacka; Chen, Rizhao (Frontiers in Plant Science, 2024)
Plants have evolved distinct defence strategies in response to a diverse range of chewing and sucking insect herbivory. While chewing insect herbivores, exemplified by caterpillars and beetles, cause visible tissue damage and induce jasmonic acid (JA)-mediated defence responses, sucking insects, such as aphids and whiteflies, delicately tap into the phloem sap and elicit salicylic acid (SA)-mediated defence responses. This review aims to highlight the specificity of defence strategies in Brassica plants and associated underlying molecular mechanisms when challenged by herbivorous insects from different feeding guilds (i.e., chewing and sucking insects). To establish such an understanding in Brassica plants, the typical defence responses were categorised into physical, chemical, and metabolic adjustments.Further, the impact of contrasting feeding patterns on Brassica is discussed in context to unique biochemical and molecular modus operandi that governs the resistance against chewing and sucking insect pests. Grasping these interactions is crucial to developing innovative and targeted pest management approaches to ensure ecosystem sustainability and Brassica productivity.